2016
DOI: 10.18632/oncotarget.12003
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that vitronectin is a potent migration-enhancing factor for cancer cells chaperoned by fibrinogen: a novel view of the metastasis of cancer cells to low-fibrinogen lymphatics and body cavities

Abstract: Diluted (1%) plasma induces migration of malignant cell lines much more strongly than potent pro-metastatic factors. To characterize the factor(s) present in diluted plasma responsible for this phenomenon we performed i) heat inactivation, ii) dialysis, iii) proteinase K treatment, and iv) molecular size filtration studies. We found that this remarkable pro-migratory activity of diluted normal plasma is associated with a ~50–100-kD protein that interacts with GαI protein-coupled receptors and activates p42/44 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…Figure 2B shows that plasma that is enriched in fibrinogen inhibits pro-migratory effect of 10% ascites whereas plasma from which fibrinogen has been chemically extracted does not possess this inhibitory activity. This confirms our previous observation that fibrinogen acts as a natural inhibitor of protein/peptide-based pro-migratory factor that is present in plasma and intestines fluids [11, 12]. …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Figure 2B shows that plasma that is enriched in fibrinogen inhibits pro-migratory effect of 10% ascites whereas plasma from which fibrinogen has been chemically extracted does not possess this inhibitory activity. This confirms our previous observation that fibrinogen acts as a natural inhibitor of protein/peptide-based pro-migratory factor that is present in plasma and intestines fluids [11, 12]. …”
Section: Resultssupporting
confidence: 91%
“…Our studies with diluted 1% plasma revealed a novel role for fibrinogen that act as chaperone of vitronectin in diluted plasma and serum [11, 12]. Therefore we decided to test whether we will observe similar inhibitory effect of fibrinogen on ascites fluid-induced migration of ovarian cancer cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations